Implementasi Restorartive Justice Melalui Upaya Rehabilitas Penyalah-guna Narkotika - Aisyah Habibah Azra (Pusat Riset dan Inovasi Nasional, 2025)
Drug abuse is a criminal act that has given rise to victims of drug abuse in society. Ideally, narcotics are needed in the world of health and science, but at the same time, the use of narcotics that is against the law is very dangerous, so legal instruments that aim to control the distribution and use of these addictive substances are very necessary. Efforts to control narcotics are carried out by providing physical punishment, fines, medical rehabilitation and social rehabilitation. Rehabilitation is regulated in Law Number 35 of 2009 concerning narcotics. This study is entitled Rehabilitation as an Effort to Overcome Narcotics Abuse. The purpose of this study is to determine the obstacles to the implementation of Rehabilitation Institutions in Law Enforcement against Drug Abusers and the reorientation of Rehabilitation Institutions in Law Enforcement against Drug Abusers based on Restorative Justice, as well as to determine Law Enforcement Against Drug Abusers Based on Restorative Justice in the future. Rehabilitation for drug abusers is a process of overcoming drug abuse dependency disorders both in the short and long term which aims to change behavior and restore individual function in society.